Red-tailed Flesh Fly, Sarcophaga haemorrhoidalis (Fallén) (Insecta: Diptera: Sarcophagidae) - Angelique Showman; C. Roxanne Connelly (EDIS, 2011)
Another insect important to forensic investigations, red-tailed flesh fly larvae invade carcasses that are in the early to advanced stages of decomposition, often arriving as early as blow flies. Learn more in this 4-page fact sheet written by Angelique Showman and C. Roxanne Connelly and published by the UF Department of Entomology and Nematology, August 2011.